A Review of Biopolymer-Based Membrane and Its Application in Oil Emulsion Wastewater Treatment - Daffa Ikhlasul Amal (Waste Technology, 2022)
This review paper will conduct mainly about oil-water emulsion treatment using biopolymer-based ultrafiltration membrane. Oil emulsion wastewater mainly use ultrafiltration process for its treatment due to its continuable process, high efficiency and low energy usage but they are relied on conventional non-degradable membrane which is made from synthetic polymer. The usage of conventional non-degradable membrane has given another waste problem in which reduces the sustainability of ultrafiltration process based on environmental perspective, therefore the degradable membrane material should be developed to increase its sustainability and reduce another waste problem. Biopolymer development has reach numbers in several years, it developing within year to year. Biopolymer such as chitosan, alginate and polylactic acid can be applied on ultrafiltration system in which it can be degradable through bio-degradation with or without modification. Modification through biopolymer in membrane fabrication for ultrafiltration will improve some characteristic that can lead to high efficiency and compability in ultrafiltration process especially for oil emulsion wastewater treatment.